DIGI-ICE: DIGITAL OFFICE ADMINISTRATION FOR BUILDING MODERN OFFICE-BASED MSMES - Nasori, Ahmad; Astarani, Dwi; Triyono, Bambang; Puspasari, Elsa (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue:This research addresses the gap in digital transformation in MSME administration, particularly the lack of easily accessible digital tools in rural areas such as Banyumas Regency, which hinders modernization. Purpose:  The goal is to develop Digi-Ice, an integrated application that combines archive management, correspondence, product cataloging, and social media integration to transform SMEs into technology-based offices. Novelty: Its main innovation lies in the rural-specific design, the integration of administrative functions and digital business, and the collaboration between Jenderal Soedirman University and MSME actors. As the first Android-compatible application, Digi-Ice reaches rural users with high accessibility. Research Methods: The research method uses the R&D model by Mckenney & Reeves (2013) through three stages: problem analysis, design, and iterative implementation. Data were collected through closed questionnaires (validated by media experts) and trials on 40 SMEs Results: The validation results showed a feasibility score of 82.3% (experts) and 82.07% (users), confirming the application's effectiveness. The main advantages include structured archiving, social media integration, and Android compatibility, although there are limitations such as reliance on the internet and the absence of an iOS version. Research Contributions: The research contributes to the digital transformation literacy of MSMEs with empirical evidence, and supports the mission of universities and the government in rural economic development. Digi-Ice has become a replicable model for local technology interventions, strengthening the competitiveness of national MSMEs in line with Indonesia's digitalization agenda.